Comparative survival benefit of currently licensed second or third line treatments for epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK) negative advanced or metastatic non-small cell lung cancer: a systematic review and secondary analysis of trials - Connock, Martin; Armoiry, Xavier; Tsertsvadze, Alexander; Melendez-Torres, G. J; Royle, Pamela; Andronis, Lazaros; Clarke, Aileen (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background A review of therapies for advanced cancers licenced by the EMA between 2009 and 2013 concluded that for more than half of these drugs there was little evidence of overall survival or quality of life benefit. Recent years have witnessed a growing number of licensed second-line pharmacotherapies for advanced/metastatic non-small cell lung cancer (NSCLC). With the aim of gauging patient survival benefit, we conducted a systematic review of randomised controlled trials (RCT) and compared survival outcomes from available licensed treatments for patients with advanced/metastatic NSCLC. Methods RCTs of second/third line treatments in participants with advanced/metastatic NSCLC and negative/low expression of Anaplastic Lymphoma Kinase (ALK) and of Epidermal Growth Factor Receptor (EGFR) were included. We searched electronic databases (MEDLINE; EMBASE; Web of Science) from January, 2000 up to July, 2017. Two or more independent reviewers screened bibliographic records, extracted data, and assessed risk of bias of studies. Published Kaplan Meier plots for OS and PFS along with restricted-mean-survival methods and parametric modelling were used to estimate the survival outcomes as mean number of months of survival. Network meta-analysis was undertaken to rank interventions and to make indirect comparisons. Results We included 11 RCTs with data for 7581 participants that compared nine different drugs. In studies of patients regardless of histology groups, targeted drugs (ramucirumab and nintedanib) yielded small overall survival gains of < 2.5 months over docetaxel, erlotinib provided no benefit, while immunotherapies (atezolizumab and pembrolizumab) delivered 5 to 6 months gain. Studies with patients stratified by histology confirmed the apparent superiority of immunotherapy (nivolumab and atezolizumab) over targeted treatments (ramucirumab, nintedanib, afatinib) providing between about 4 to 8 months OS gain over docetaxel. In network analysis immunotherapies consistently ranked higher than alternatives irrespective of population histology and outcome measure. Conclusion Our review indicates that nivolumab, pembrolizumab and atezolizumab provide superior survival benefits compared to other licensed drugs for late stage NSCLC. Patient gains from these immunotherapies are substantial compared to the expected average survival with chemotherapy (docetaxel) of < 1 year for people with squamous histology and about 1.25 year for those with non-squamous histology.